PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DIREKTORAT JENDERAL PENDIDIKAN SEKOLAH MENENGAH ATAS KEMENTERIAN PENDIDIKAN, BUDAYA, RISET DAN TEKNOLOGI JAKARTA SELATAN - Nasiroh; Nariah (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of work environment and work discipline on the performance of employees of the Directorate General of Senior High School Education of the Ministry of Education, Culture, Research and Technology, South Jakarta, both partially and simultaneously. The method used in this study is quantitative. This study was conducted on 60 employees using probability sampling techniques. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis test which were analyzed using SPSS 24 program. The results of the study are as follows: The results of simple regression test showed that work environment has a positive and significant effect on employee performance with the regression equation Y = 14,535 + 0,587 X1, the correlation value is 0.597, meaning that the two variables have a moderate level of relationship. The value of the coefficient of determination is 35.6%. The partial hypothesis test of the work environment variable obtained Tcount>Ttable, namely 3,017> 2,002. Thus H01 is rejected and Ha1 is accepted, meaning that there is a significant influence of work environment on employee performance. The analysis of the work discipline variable has a positive and significant effect on employee performance with the regression equation Y = 15,811 + 0,555 X2. The correlation value is 0.559, meaning that the two variables have a moderate level of relationship. The value of the coefficient of determination is 31.2%. The hypothesis test obtained Tcount>Ttable, namely 2,200> 2,002. Thus H02 is rejected and Ha2 is accepted, meaning that there is a significant influence of The Work Discipline on Employee Performance. The third analysis obtained the regression equation Y = 10,910 + 0,398 X1 + 0,293 X2. The correlation value is 0.638, meaning that the independent variable with the dependent variable has a strong relationship. The value of the coefficient of determination is 40.7%, while the remaining 59.3% is influenced by other factors. The hypothesis test obtained the value of Fcount > Ftable or (19,549 > 3.16). Thus H03 is rejected and Ha3 is accepted. This means that there is a significant influence of work environment and work discipline on employee performance simultaneously.